Implikasi Makna dalam Terjemahan Unsur Budaya: Analisis Terhadap Hadis Sahih Bukhari - Lubna Abd Rahman; Arnida A. Bakar; Sulhah Ramli; Muhamad Arif Asnawi bin Mat Zaki (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia